(untitled) (Web of Teachers: Inderscience Research, 2025)
The process of globalization is increasing the interaction between different countries, economic systems, cultures and languages. The German language, as a language with historically strong political and economic influence, plays an important role in the globalization process. This article analyzes the role of the German language in the globalization process, its impact in the economic, scientific, cultural and communicative spheres. The global influence of the German language, its role in international relations, scientific research, business and culture are examined in detail. The article also analyzes the relations between the German language and other languages.